Perceptions of Turkish entrepreneurs and employees about Hungarian business environment and attitudes - Mehmet Sercan Onalan; Robert Magda (Open Economics, 2018)
Since the enrolment of Turkey in the Customs Union, Turkish exporters start to explore the Hungarian market and day by day increased the volume of trade between those two nations. In this case, the location of Hungary had a significant role, not just for the internal market but also potential to have trade with neighbour countries. Today, partially, the opportunities in Hungary are starting to become noticed by Turkish entrepreneurs. In the last decade, the main characteristic of the Turkish in Hungary is that they went to this country as entrepreneurs. The main characteristic that distinguishes the Turks living in Hungary from other European countries is that they are entrepreneurs, not workers. The aim of this research is to reveal the differences between the perceptions of Turkish entrepreneurs and employees of Hungarian business environment and attitudes towards Turkish entrepreneurship. This study was carried out on a total of 102 participants who were divided into two equal groups in terms of the number of participants. In results, it has been found out that employees and entrepreneurs has been differed by educational level, duration time in Hungary and sector which they operate. In short, the motivation of employees to be an entrepreneur is low.
Keywords: 330; business environment; commercial relations; Hungary; Turkish employees; Turkish entrepreneurs; Turkish expats